Проблеми екологічного моніторингу освоєння сланцевого газу на Волино-Поділлі - Багрій, І.Д.; Чепіль, В.П.; Стародубець, К.М. (Геоінформатика, 2015)
Сучасні технології розробки сланцевого газу ґрунтуються на гідравлічному розриві пласта, застосування якого несе в собі численні екологічні ризики для довкілля. Внаслідок таких робіт на перспективній території Волино-Поділля можуть проявлятися несприятливі екологічні процеси, а саме забруднення підземних джерел питної води, проникнення на поверхню технологічних розчинів і газу, активізація техногенних землерусів і зсувів. З метою їх попередження проведено роботи з виявлення і картування ділянок екологічних ризиків. Виділено охоронні зони, зокрема системи водозаборів, місцевих агломерацій тощо. Запропоновано засоби поетапної оптимізації існуючої мережі спостережень у вигляді одного поздовжнього регіонального профілю північно-західного простягання та кількох поперечних, що проходитимуть з південного заходу на північний схід. Современные технологии разработки сланцевого газа базируются на гидравлическом разрыве пласта, использование которого несет в себе многочисленные экологические риски для окружающей среды. В результате таких работ на перспективной территории Волыно-Подолья могут проявляться неблагоприятные экологические процессы, а именно загрязнение подземных источников питьевой воды, проникновение на поверхность техноло¬гических растворов и газа, активизация техногенных землетрясений и сдвигов. С целью их предупреждения проведены работы по выявлению и картированию участков экологических рисков. Выделены охранные зоны, в частности системы водозаборов, местных агломераций и др. Предложены пути поэтапной оптимизации существующей сети наблюдений в виде одного продольного регионального профиля северо-западного простирания и нескольких поперечных, которые будут проходить с юго-запада на северо-восток. Purpose. The purpose of the paper is to study and map of the areas with enhanced environmental hazards of Volyno- Podillya, where gas production is not recommended; to develop optimization stages for the existing network of hydroecological monitoring of the given area.
Design/methodology/approach. The studies were conducted using structural-thermo-atmo-geochemical method that allows selecting and mapping zones of high fracturing rocks.
Findings. We defined and mapped modern active tectonic lineaments of various rank and related areas of tectonic fractures and crushing which create zones of formational permeability. We also defined conservation areas, such as water intake systems and local agglomerations, where work on shale gas production is not recommended. Special attention was given to river areas confined to zones of faults and decompression of the rocks. The authors propose, while choosing the objects of further geological exploration for shale gas, give special consideration to the selected areas of environmental risk. The analysis of installing a modern groundwater monitoring network showed to optimize works for the development of shale gas resources with regard to the state of the mining works, water placement, and the groundwater regime.
Practical value/implications. Implementation of the proposed optimization of the environmental monitoring system would significantly reduce the risk of environmental effects of shale gas development in the Volyno-Podolia. The exact prediction of various ecological processes is possible only after the optimization of the existing monitoring network using geographic information systems and simulation of hydrogeological conditions of the territory.